Holocene ice recession at Polygon Spur, Reedy Glacier, Antarctica. (January 2017) - Hall, Brenda; Bromley, Gordon; Stone, John; Conway, Howard
The Holocene history of outlet glaciers affords information on the behavior and mechanisms controlling the extent of the East Antarctic Ice Sheet. Here, we present both new radiocarbon and recalculations of previously published cosmogenic exposure-age data that constrain Holocene ice dynamics along upper Reedy Glacier in the southernmost Transantarctic Mountains. Ice remained at or close to its last glacial maximum position until the early Holocene, at which time it underwent thinning. A period of apparent relative stability in the mid-Holocene led to the formation of ice-dammed proglacial ponds, as well as of moraines located roughly two-thirds of the distance from the maximum position to the present-day ice margin. Renewed thinning began after 3600 yr BP, with ice reaching present-day levels by 2400 yr BP. Ice variations along upper Reedy Glacier likely reflect the balance between upstream propagation of mechanical thinning events at the glacier mouth and regional accumulation changes.